Potential Connections between Migration and Immigrants’ Food Consumption Habits. The Case of Romanian Immigrants in Andalusia, Spain - Andreea Simona Săseanu; Raluca Mariana Petrescu (Amfiteatru Economic)
The paper aims to identify potential connections between migration and food consumption habits of Romanian immigrants in Andalusia, Spain and to study a series of factors that may contribute to the establishment of these connections. The analysis was based on a series of information obtained through a field research carried out between January and June 2011 among the Romanian immigrants in Andalusia (306 respondents). The analysis’ results revealed the fact that after migration, the Romanian immigrants who took part in the study felt a series of changes in their food consumption habits, mainly resulting in consuming a higher proportion of the food products specific to the host country, compared to the food products specific to their country of origin. The analysed factors that may influence the relationship between migration and food consumption habits were encountered in the specific scientific literature, namely the length of residence and immigrants’ age. The analysis revealed the fact that among different groups of respondents by length of residence and age, there are statistically significant differences in what concerns their perception regarding the changes in their food consumption habits after migration. The length of residence is positively correlated with the changes in food consumption after migration, while age is negatively correlated.